The History, Present and Future of the Translation Industry in Uzbekistan - Tilavov Ikhtiyor Makhmud ugli (Global Scientific Publishing, 2023)
The birth of translation as a special type of human activity goes back to ancient times, even in pre-literate times, when the first contacts began between multilingual tribes. The emergence of professional translators, the increase in the importance of translation activities can be attributed to the time of the emergence of early states in the Ancient East and the establishment of trade, political and cultural relations between them. Thus, this article examines and analyzes the history, present and future of translation in Uzbekistan. The Uzbek translation, which has a thousand-year history, also achieved unprecedented results in the last century, introduced our people to the royal works of world literature. During the century, a number of major translations were made, including: Chulpon - Shakespeare ("Hamlet"), Usman Nasir - Lermontov ("Demon"), Oybek - Pushkin ("Eugene Onegin"), Erkin Vakhidov - Goethe ("Faust"), Abdulla Oripov- Dante ("Hell"), Kadir Mirmukhamedov- Gomer ("The Iliad"). These translations were an important event in the history of our literature, moreover, they became stable translations of these works into our language.
Keywords: literature; translation; method; history